Yougui Pills Attenuate Cartilage Degeneration via Activation of TGF-β/Smad Signaling in Chondrocyte of Osteoarthritic Mouse Model - Zhang, Lei; Wang, Ping-er; Ying, Jun; Jin, Xing; Luo, Cheng; Xu, Taotao; Xu, Shibing; Dong, Rui; Xiao, Luwei; Tong, Peijian; Jin, Hongting (Frontiers in Pharmacology, 2017)
Yougui pills (YGPs) have been used for centuries in the treatment of Chinese patients with Kidney-Yang Deficiency Syndrome. Despite the fact that the efficiency of YGPs on treating osteoarthritis has been verified in clinic, the underlying mechanisms are not totally understood. The present study observes the therapeutic role of YGPs and mechanisms underlying its chondroprotective action in osteoarthritic cartilage. To evaluate the chondroprotective effects of YGPs, we examined the impact of orally administered YGPs in a model of destabilization of the medial meniscus (DMM). Male C57BL/6J mice were provided a daily treatment of YGPs and a DMM surgery was performed on the right knee. At 12 weeks post-surgery, the joints were harvested for tissue analyses, including histomorphometry, OARSI scoring, micro-CT and immunohistochemistry for COL-2, MMP-13 and pSMAD-2. We also performed the relative experiments mentioned above in mice with Tgfbr2 conditional knockout (TGF-βRIICol2ER mice) in articular cartilage. To evaluate the safety of YGPs, hematology was determined in each group. Amelioration of cartilage degradation was observed in the YGPs group, with increases in cartilage area and thickness, proteoglycan matrix, and decreases in OARSI score at 12 weeks post surgery. In addition, reduced BV/TV and Tb. Th, and elevated Tb. Sp were observed in DMM-induced mice followed by YGPs treatment. Moreover, the preservation of cartilage correlated with reduced MMP-13, and elevated COL-2 and pSMAD-2 protein expressional levels were also revealed in DMM-induced mice treated with YGPs. Similarly, TGF-βRIICol2ER mice exhibited significant OA-like phenotype. However, no significant difference in cartilage structure was observed in TGF-βRIICol2ER mice after YGPs treatment. Interestingly, no obvious adverse effects were observed in mice from each group based on the hematologic analyses. These findings suggested that YGPs could inhibit cartilage degradation through enhancing TGF-β/Smad signaling activation, and be considered a good option for the treatment of osteoarthritis.